The relative diagnostic yields of clinical, FOTI and radiographic examinations for the detection of approximal caries in youngsters - Mialhe Fabio; Pereira Antonio; Meneghim Marcelo; Ambrosano Glaucia; Pardi Vanessa (Wolters Kluwer Medknow Publications, 2009)
Background: The detection of carious lesions in the initial stages of development is very important in order to prevent the occurrence of cavitation. Aims and Objectives: The aim of the present study was to compare three methods-visual examination, FOTI, and bitewing radiographic examination-for the detection of noncavitated and cavitated approximal carious lesions. Materials and Methods: Seventy students (mean age 14 years) with low caries prevalence were examined by three examiners. The tooth surfaces judged as having caries by at least one examiner or one diagnostic method were scheduled for tooth separation. Results: The results showed that the incorporation of FOTI and radiographic examination represented an additional diagnostic yield of 50% and about 110%, respectively, compared to clinical examination alone. Conclusion: We conclude that FOTI or radiographic examination, or both, used as adjuncts to clinical examination, could improve the detection of noncavitated and cavitated approximal carious lesions. Although FOTI should not replace bitewing radiographic examination, it does seem to have additional value for the detection of carious lesions on approximal surfaces of the posterior teeth in school children with low caries prevalence.